The correlation between dental caries and serum iron (Fe) levels in female students of Mamba’ul Khoiriyatil Islamiyah (MHI) Madrasa in Jember, East Java, Indonesia - Ristya Widi Endah Yani; Taufan Bramantoro; Farida Wahyuningtyas; Talitha Zulis Islaamy (Dental Journal (Majalah Kedokteran Gigi), 2020)
Background: Dental caries may cause discomfort and pain when chewing food, which in turn leads to insufficient absorption of nutrients, including iron, by the body. Lack of iron intake can cause iron-deficiency anaemia. Iron deficiency may also decrease salivary secretion and buffer capacity due to reduced salivary gland function, which may lead to dental caries. Purpose: This study aims to analyse the correlation between dental caries and serum iron (Fe) levels in the students of Mamba’ul Khoiriyati Islamiyah (MHI) Madrasa Aliyah in Bangsalsari Jember. Methods: Out of 71 students aged 15-18 years, 24 students were examined for caries with the DMF-T index and blood samples were also collected using the phlebotomy technique to assess the serum iron (Fe) level in µg/dL. The data were analysed using the Spearman’s correlation test (α = 0.05). Results: The average DMF-T score was high (7 ± 3.4) and the average serum iron (Fe) level was below normal (38 ± 11.5 µg/dL). The Spearman’s correlation test for dental caries and serum iron (Fe) levels showed significant results (p <0.05). Conclusion: The occurrence of dental caries correlates with serum iron (Fe) levels. The higher the level of serum iron (Fe), the lower the level of dental caries.